Pengaruh Non Performing Loan, Return On Asset, Dan Capital Adequacy Ratio Terhadap Harga Saham - Andini Nur Madaniah; M. Mustaqim (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Investors need to consider several factors before making an investment, such as stock price volatility. A company's share price can be an indicator of its managerial performance. For issuers, gaining the trust of investors or potential investors is a very profitable thing because it can increase the desire to invest in issuers. To find out the effect of financial parameters, especially NPL, ROA, and CAR on stock prices is the purpose of the research. Secondary data may include the financial statements of banking organizations that are listed on the IDX during a period of five years, beginning in 2018 and ending in 2022. The technique of purposive sampling is utilized in this study, which employs quantitative methodology as its approach. The techniques of multiple linear regression analysis are utilized in the data analysis process. The research findings indicate that stock prices are impacted by the Return On Asset and Non Performing Loan. But on the contrary, the stock price is not affected by the Capital Adequacy Ratio. Keywords: NPL, ROA, CAR, Stock Price